Avaliação dos efeitos do exercício físico associado à suplementação com vitamina D na lesão estriatal unilateral por 6-OHDA em ratos - Costa, Roberta Oliveira da (2022)
Parkinson's disease (PD) is a neurodegenerative disorder caused by the loss of dopaminergic cells in the nigrostriatal pathway, with a marked reduction in dopamine (AD) content in the striated body. In the search for new treatment strategies, physical exercise and vitamin D (VD) supplementation has shown numerous benefits for the brain, and can act as a modulator of neurogenesis, neuronal plasticity, besides presenting a strong antioxidant activity. In this scenario, the present study aimed to evaluate the effects of physical exercise associated with VD supplementation on unilateral striatal injury by 6-Hydroxydopamine (6-OHDA) in rats. For this purpose, male Wistar rats were distributed into 6 groups: false operated (FO) without exercise (S/E), false operated (FO) with exercise (C/E), 6-OHDA without exercise (S/E), 6-OHDA with exercise (C/E), 6-OHDA with exercise (S/E) and with VD, 6-OHDA with exercise (C/E) and VD, who received injections of 6-OHDA (12 μg/2μl) or saline solution (FO), in the right striatum through stereotactic surgery. The exercise protocol was performed for 21 days, for 30 min on a treadmill, with a speed of 20 cm/s starting 24 hours after the surgical procedure. Oral administration of VD occurred daily at a volume of 0.1 mL/10 g of weight. The dose used in the animal VD (1μg/kg/day) for 21 days. After the application of treatment protocols, the animals were submitted to behavioral tests (apomorphine, rotarod, open field, cylinder, ymaze, object recognition) and euthanized, the cerebral areas, prefrontal cortex (CPF), hippocampus (HP) and striated body (CE) used for neurochemical and immunohistochemical determinations. Behavioral and neurochemical data were analyzed by the Shapiro-Wilk test to verify normality. The nonparametric data evaluated using the Kruskal-Wallis test followed by Dunn's post-hoc test, while parametric data were analyzed by variance analysis (ANOVA) of a pathway, followed by tukey's post-hoc test for multiple comparations. In all analyses, p<0.05 values were considered statistically significant. The results showed that physical exercise associated with VD supplementation reduced rotational behavior induced by apomorphine, and protected from motor and cognitive deficits (working memory and short duration). In addition, AD levels have increased. As for oxidative stress, it promoted a reduction in malonodialdehyde (MDA) contents and nitrite/nitrate production and increased GSH concentrations. In the immunohistochemical study, physical exercise and VD supplementation prevented the death of dopaminergic neurons in the injured striated body, and increased immunoreactivity for Tyrosine hydroxylase (TH), Dopamine Transporter (DAT) and Glial-derived neurotrophic factor (GDNF). As well as, the inhibition of immunoreactive neurons for glial fibrillar acid protein (GFAP) and Alpha-synuclein. In conclusion, we showed that behavioral and neurochemical changes in Hemiparkinsonian rats were prevented with the application of physical exercise and vd supplementation, attenuating the decrease in AD concentrations in the striatum, characterizing a potential neuroprotective effect in the experimental PD model.